Etanercept overview of clinical experience in the treatment of psoriasis and psoriatic arthritis. (April 2011) - Bachmann, Frank; Kokolakis, Georgios; Sterry, Wolfram; Philipp, Sandra
Biologics have revolutionized the management of psoriasis and psoriatic arthritis. Etanercept was the first biologic to be approved in Europe for the treatment of psoriatic arthritis in 2002 and since 2005 has been approved for the treatment of psoriasis as well. This provides approximately 8 years of experience in the treatment of psoriasis, nearly a decade, which prompted us to review the available data with a special focus on dermatology and compare it with other existing treatment modalities. The aim of this article is to give an update on etanercept with emphasis on information that is important for practical daily use. Most data are based on high-quality studies and official guidelines but, if necessary, data from recent publications or clinical expertise have also been added.